Tingkat Kepatuhan Pasien Diabetes di Klinik Ide Indramayu - Fenny Evira; Moh Rizky Adriansyah (Syntax Corporation Indonesia, 2021)
Diabetes Mellitus (DM) is a disease caused by the body's inability to make or use insulin properly. Diabetes mellitus (DM) is a complex chronic disease characterized by elevated blood glucose levels or hyperglycemia, which occurs as a result of failure of insulin secretion, decreased insulin secretion or insulin resistance. The purpose of the study was to find out the picture of diabetes patients' compliance with therapy using diabetes drugs at Ide Indramayu Clinic. This type of research is research that is descriptive with case series design methods that are a collection of individual cases of a disease with the same diagnosis. The type of data method collected is secondary data that has been recorded on medical records (status cards) of people with diabetes Mellitus who seek road treatment in Kinik Ide. The proportion of the rate of fertility of diabetic patients in Ide Clinic is based on sociodemographic, the highest proportion is in the age group of 51-58 years 40%, female sex 65%, Javanese 85%, Islam 95%, based on work/IRT / pension as much as 45%, residence 100% of indramayu population.